Pendidikan Dan Model Pengelolaan Konflik - Alfin Nabila; Nabila Rosidah; Lucky Salama; Firda Jannani; Mu’alimin Mu’alimin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Conflict in the educational context is a phenomenon that needs special attention, because it can have an impact on the learning process and the school environment as a whole. In this literature, we review various conflict management models that have been identified and applied in educational contexts. This research aims to understand the role of these models in increasing educational effectiveness, minimizing learning disruptions, and creating an environment conducive to student growth. we consider conflict management models at the administrative and policy levels. In an educational context, conflict can arise in policy determination, resource allocation, or curriculum issues. These models include the involvement of all stakeholders, careful monitoring and evaluation, and a dialogic approach to the decision-making process. Research shows that conflict management at the administrative and policy levels can produce more inclusive and sustainable policies and improve the overall quality of education. In this literature, we highlight how important it is to understand and apply conflict management models in educational contexts. Effective conflict management can create an educational environment that is more conducive to learning, improve the quality of teaching, and help students develop constructive conflict resolution skills. These models can become the basis for more inclusive, equitable and effective education.